ENT 530 Business Model Canvas: Sya Cakery / Nur Auni Rushda A'spuri ... [et al.] - A'spuri, Nur Auni Rushda; Mohd Suhaimi, Saidatul Suhailah; Ahmad Murad, Nur Fazira; Rostam, Muhammad Raziq; Timun, Finarioson; Muhammad Amirul Ridhzuan Stanny, Syahmi Zaini (2021)
Sya Cakery is a business that is owned by Nur Syafiqah Afendi, and the nature business of Sya Cakery is sole proprietorship. This business was established in September 2019, and is located in Bagan Serai, Perak. Sya Cakery sells homemade desserts with a number of custom orders of their products. It is an interesting business to venture along the entrepreneurs path as a personal own business at a young age. This business provides very good customer service for its beloved customers, for instance, bringing in a positive and friendly environment for every customer that comes to Sya Cakery. Most of Sya Cakery products are promoted in social media Instagram. It will make it easier for the customers to find Sya Cakery as most individuals these days are more active in social media and on the internet. The purpose of choosing Sya Cakery for our research is to learn and understand how to manage a business well, figuring out how to overcome and solve problems encountered, as well as having a clearer view on how to conduct and start a business, thus achieving a successful business journey. The benefits of Sya Cakery using the Business Model Canvas (BMC) enables her to visualize and identify key elements of business such as the value propositions, customers, business operations and finances. Hence, deciding what is necessary to be focused on would help save time and develop more knowledge and experiences of the business.